2010
DOI: 10.1111/j.1440-1843.2010.01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea is associated with risk factors comprising the metabolic syndrome

Abstract: Although Asians are generally less obese than Caucasians, the prevalence of the MS was high among Japanese patients with OSA, and even among non-obese patients, OSA was associated with risk factors for the MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
5
22
1
3
Order By: Relevance
“…If the same results were to be shown in humans with OSA, the patients without any metabolic syndrome component may represent a low-risk subgroup, with obvious consequences regarding treatment. Some studies, however, found metabolic abnormalities in non-obese OSA patients, although a diagnosis of metabolic syndrome was not fulfilled [19,28,37]. Conversely, both morbidly obese patients [38] and patients with the metabolic syndrome [26] showed worse metabolic variables associated with severe OSA compared with subjects without OSA.…”
Section: Prevalence Of the Metabolic Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…If the same results were to be shown in humans with OSA, the patients without any metabolic syndrome component may represent a low-risk subgroup, with obvious consequences regarding treatment. Some studies, however, found metabolic abnormalities in non-obese OSA patients, although a diagnosis of metabolic syndrome was not fulfilled [19,28,37]. Conversely, both morbidly obese patients [38] and patients with the metabolic syndrome [26] showed worse metabolic variables associated with severe OSA compared with subjects without OSA.…”
Section: Prevalence Of the Metabolic Syndromementioning
confidence: 99%
“…Clinical studies in OSA patients have reported variable prevalence of the metabolic syndrome according to NCEP-ATP III criteria, with values ranging between 23% and 87% [14][15][16][17][18][19]. The largest published series (819 Japanese patients) found prevalence of the metabolic syndrome to be 49.5% in males and 32% in females [15].…”
Section: Prevalence Of the Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…3). MetS is diagnosed in clinical practice by the NCEP-ATP (National Cholesterol Education ProgrammeAdult Treatment Panel) III criteria, which require the presence of three out of five criteria [36][37][38][39][40][41][42][43][44][45]. The number of MetS criteria is defined as the metabolic index and can be used as an indicator of severity of metabolic abnormalities.…”
Section: Osa Visceral Fat and The Metabolic Syndromementioning
confidence: 99%
“…Se postula que los eventos secundarios a la fragmentación del sueño, la HI y el aumento de la actividad simpática contribuyen a este "desbalance metabólico" aumentando significativamente el riesgo cardiovascular 8 . En un estudio de pacientes con diagnóstico reciente de SM, 68% de ellos presentaba SAOS como comorbilidad 15,16 . En otro estudio, que incluyó a 195 pacientes con patología cardiovascular, el SM fue el principal predictor de la desaturación nocturna 6 .…”
Section: Síndrome Metabólico (Sm)unclassified